2013
DOI: 10.2754/avb201382030237
|View full text |Cite
|
Sign up to set email alerts
|

Weissella viridescens in meat products – a review

Abstract: Although ubiquitous, bacteria of the Weissella genus are not given sufficient attention. Many members of the genus were originally classified as Leuconostoc or Lactobacillus. With the development of molecular methods, these phylogenetically closely related bacteria formed a separate group, the Weissella genus. Due to its heterofermentative metabolism, Weissella spp. may cause considerable damage particularly in the meat industry. Slime formation and greening of meat products are sensory defects for which the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
(44 reference statements)
1
8
0
1
Order By: Relevance
“…These bacteria were analysed using the API 50 CHL (bioMérieux, France) test system according to the protocol set by the manufacturer, and they were defined as: LB37, W. viridescens; LB49, L. sakei; M17, P. acidilactici; and M24, L. plantarum. These results were in agreement with the data reported in the literature (23,(27)(28)(29).…”
Section: Characterization Of the Lactic Acid Bacteriasupporting
confidence: 93%
“…These bacteria were analysed using the API 50 CHL (bioMérieux, France) test system according to the protocol set by the manufacturer, and they were defined as: LB37, W. viridescens; LB49, L. sakei; M17, P. acidilactici; and M24, L. plantarum. These results were in agreement with the data reported in the literature (23,(27)(28)(29).…”
Section: Characterization Of the Lactic Acid Bacteriasupporting
confidence: 93%
“…Leuconostoc spp. and Leuconostoc-like microorganisms, such as Weissella viridescens, may cause meat products to turn green, due to the formation of hydrogen peroxide, which oxidizes nitrosomyochromogen as the consequence of the exposure of meat to O2 (Dušková et al, 2013). S. putrefaciens may determine green discolouration in vacuum-packed meat (Doulgeraki et al, 2012).…”
Section: Colour Alterationmentioning
confidence: 99%
“…W. viridescens may be the cause of ropy slime formation or meat turning green. After the appearance of individual colonies on a wet surface, a continuous layer of greenish slime is formed (Dušková et al, 2013).…”
Section: Filaments and Ropy Slimementioning
confidence: 99%
“…The previous report of Charteris et al (1998) showed resistance of LAB to bacitracin at 10 U. Duskova and Karpiskova (2013) reported that fifteen strains of lactobacilli (17%) isolated from fermented foods were resistant to at least one antimicrobial agent, and one strain was multi resistant. The resistance profile was calculated based on zone size interpretative chart for antibiotics as per CLSI (2011).…”
Section: Sof-43mentioning
confidence: 97%